Etika Kepemimpinan Kristen dalam Penggunaan Kecerdasan Buatan (AI) pada Pelayanan Gereja Modern - Anthony (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
The rapid development of Artificial Intelligence (AI) has transformed various sectors of human life, including church ministry and religious organizational management. This study aims to analyze Christian leadership ethics in the use of AI within modern church ministry. The research employs a qualitative descriptive method through theological literature review and analysis of recent studies concerning digital technology and pastoral ministry. The findings indicate that AI provides significant benefits for church administration, digital communication, congregational data management, and online evangelism. Nevertheless, ethical challenges also emerge, such as the weakening of pastoral relationships, data privacy concerns, algorithmic bias, and the risk of dehumanization in ministry practices. From a Christian theological perspective, ministry is fundamentally relational and incarnational, reflecting the example of Jesus Christ who ministered through personal presence, compassion, and direct interaction with people. Therefore, AI should be understood as a supportive instrument rather than a substitute for spiritual authority and pastoral presence. Christian leadership in the digital age must be grounded in integrity, transparency, spiritual discernment, and respect for human dignity as the image of God (imago Dei). This study contributes to the development of ethical guidelines for churches in utilizing AI responsibly while maintaining theological integrity and Christian spiritual values.